Eating school meals daily is associated with healthier dietary intakes: The Healthy Communities Study - Au, Lauren E (J Acad Nutr Diet, 2018)
BACKGROUND: Research on the association between school meal consumption and overall dietary intake post-Healthy Hunger-Free Kids Act implementation is limited. OBJECTIVE: This study examines the association between frequency of participating in the National School Lunch and School Breakfast Programs and children’s dietary intakes. DESIGN: The Healthy Communities Study was a cross-sectional observational study conducted between 2013–2015. PARTICIPANTS/SETTING: U.S. children ages 4–15 years (n=5,106). MAIN OUTCOME MEASURES: Dietary measures were assessed using the National Health and Nutrition Examination Survey Dietary Screener Questionnaire. Dietary intake included fruit/vegetables, fiber, whole grains, dairy, calcium., total added sugar, sugar-sweetened beverages, and energy-dense foods of minimal nutritional value. STATISTICAL ANALYSIS: Multivariate statistical models assessed associations between frequency of eating school breakfast or lunch (every day vs. not every day) and dietary intake, adjusting for child and community-level covariates. RESULTS: Children who ate school breakfast every day compared to children who ate 0–4 days/week, reported consuming more fruits/vegetables (0.1 cup/day, 95% CI: 0.01, 0.1), dietary fiber (0.4 g/day, 95% CI: 0.2, 0.7), whole grains (0.1 oz/day, 95% CI: 0.05, 0.1), dairy (0.1 cup/day, 95% CI: 0.05, 0.1), and calcium (34.5 mg/day, 95% CI: 19.1, 49.9). Children who ate school lunch every day compared to those who ate less frequently, consumed more dairy (0.1 cup/day, 95% CI: 0.1, 0.2) and calcium (32.4 mg/day, 95% CI: 18.1, 46.6). No significant associations were observed between school meal consumption and energy-dense nutrient poor foods or added sugars. CONCLUSIONS: Eating school breakfast and school lunch every day by U.S. schoolchildren was associated with modestly healthier dietary intakes. These findings suggest potential nutritional benefits of regularly consuming school meals.